2012
DOI: 10.1186/1472-6963-12-148
|View full text |Cite
|
Sign up to set email alerts
|

Centralisation of services for children with cleft lip or palate in England: a study of hospital episode statistics

Abstract: BackgroundIn 1998, a process of centralisation was initiated for services for children born with a cleft lip or palate in the UK. We studied the timing of this process in England according to its impact on the number of hospitals and surgeons involved in primary surgical repairs.MethodsAll live born patients with a cleft lip and/or palate born between April 1997 and December 2008 were identified in Hospital Episode Statistics, the database of admissions to English National Health Service hospitals. Children we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
5
44
0
1
Order By: Relevance
“…Several studies have indicated that a higher surgeon volume is related to favorable outcomes in cleft surgery. [3][4][5][6] Another study has reported a relation between a higher surgeon volume and shorter duration of anesthesia. 13 However, the association between hospital volume and outcomes of cleft lip and palate surgery remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that a higher surgeon volume is related to favorable outcomes in cleft surgery. [3][4][5][6] Another study has reported a relation between a higher surgeon volume and shorter duration of anesthesia. 13 However, the association between hospital volume and outcomes of cleft lip and palate surgery remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Centralization results in a lower rate of corrective surgery, a shorter in-hospital stay, and standardization of the timing of surgery. 6,7 However, these studies did not account for possible effects of hospital volume or surgeon volume on the outcomes of surgery for cleft lip and palate because of their before-versus-after study design and limited adjustment for confounders. In addition, a few years after centralization, 1 study reported that surgeon volume did not affect the outcomes of cleft repair.…”
mentioning
confidence: 99%
“…This paper considers parent's perceptions of appearance and treatment outcomes in their 5-year-old child with cleft lip and palate Children born with a cleft lip and palate (CLP) undergo a number of procedures and surgical interventions during their first years of life, which are carried out to correct and improve oral function, speech, and facial appearance. Studies have quantified the burden of hospital care for children with CLP [2,3], and surgical treatment can be a frightening experience for a child [4]. Few, if any studies have, however, explored parents' perceptions of how their child cope with cleft surgery and treatment-related stress, while also comparing this information with registered postsurgical complications and surgical technique.…”
Section: Introductionmentioning
confidence: 99%
“…La revue de la littérature concernant ces associations malformatives au sein de populations géographiquement et socioéconomiquement proches a rapporté des taux de 21 % en Angleterre sur une revue de 10 892 patients[8], 33 % en Italie dans une étude de 200 cas[11] et 36 et 34 % dans l'Est de la France respectivement au sujet de 207 patients[2] et 321 patients…”
unclassified